The Turkish economy in a regional perspective - Secil Pacaci Elitok; Thomas Straubhaar (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
The end of the Cold War changed the political landscape of the Black Sea area and the Middle East completely: In the North-East, the collapse of the Soviet Union was followed by the nascence of new sovereign nation states - with all the problems of nation building and all the costs of going through a fundamental economic and social transformation from communist systems to market oriented economies. In the West, the European Union (EU) widened geographically and deepened structurally, increasing the number of full members from 12 to 15 (1995) to 25 (2004) and finally to 27 (2007). Furthermore a European Monetary Union with a common currency for 16 members was established. Finally, the South-East - disturbed by political crisis and wars - has become more important as a supplier of energy (i.e. gas and oil) not only for the area itself but even more for Europe and other world regions.
Keywords: 330